(untitled) (Journal of Applied Botany and Food Quality, 2012)
The triazole fungicide triadimenol is known to have plant growth regulator (PGR) activity in cereals when applied as a seed dressing. The effect of environmental conditions on PGR activity of triadimenol, other triazoles (flutriafol, prothioconazole, tebuconazole), the benzimidazole fuberidazole, imidazoles (imazalil, prochloraz), and the strobilurin fluoxastrobin on barley (Hordeum vulgare) was investigated using commercial seed dressings also including pyrimethanil (anilinopyrimidine) and triazoxide (benzotriazine), under controlled conditions. Irrespective of temperature or soil water content (SWC) triazole-containing seed treatments had a significant effect on the time and rate of plant emergence. Both triadimenolcontaining products significantly reduced the length of subcrown internodes and resulted in reduced shoot length three weeks after sowing. Growth suppression was stronger under optimal environmental conditions (17 to 19°C, 60 % SWC). Under suboptimal conditions – 9 to 10°C and 40 % SWC, respectively – no differences in shoot length were detected five weeks after sowing, whereas under optimal conditions plant growth retardation was still significant. The flutriafol-containing product partly inhibited shoot elongation, but never affected dry mass accumulation and root growth. The strobilurin-containing seed dressing had no marked plant growth activities on seedling emergence, shoot length and subcrown internode, but slightly stimulated root growth under all environmental conditions. The results indicate varying PGR activities of triazole seed dressings in response to mixing partner and growth conditions and suggest an increased stress tolerance of seedlings treated with triadimenol, enabling barley to better cope with suboptimal environmental conditions.